Research progress on processing of thermoelectric materials by mechanical alloying combined with spark plasma sintering - SHI Jian-lei; PEI Jun; ZHANG Bo-ping; LI Jing-feng (Fenmo yejin jishu)
The great progress has been made in the research of the thermoelectric (TE) materials in recent years. The thermoelectric properties of the traditional Bi2Te3 and PbTe based materials have been improved, and a series of the original high-performance thermoelectric materials, such as SnSe and GeTe, have also been discovered. The thermoelectric properties of the thermoelectric materials not only depend on the composition, structure, and defects of the materials, but also are closely related to the preparation process. Mechanical alloying (MA) combined with spark plasma sintering (SPS) is an important method to synthesize the thermoelectric materials, which is simple and efficient to obtain the fine-grained microstructures and the nanostructures, leading to the reduced lattice thermal conductivity and the enhanced thermoelectric properties. In addition, the prepared bulk materials have the better mechanical properties, which can effectively enhance the life-time of the thermoelectric devices. The basic principle and key influencing factors of the thermoelectric material preparation by mechanical alloying and spark plasma sintering were introduced in this paper, and the research progress of the telluride, sulfide, and selenide based thermoelectric materials prepared by this method was summarized.